Structured review of validity of clinical definitions of hypoxic-ischaemic encephalopathy (HIE). (7th June 2011) - Harijan, P D; Boyle, E M; Kurinczuk, J J; Jaspan, T; Anumba, D O C; Draper, E S
Abstract : Hypoxic-ischaemic encephalopathy (HIE) incidence is an important perinatal care quality measure as it is a near-miss marker of intrapartum-related stillbirth and neonatal death. Currently there are worldwide clinical and epidemiological HIE case definition inconsistencies. This has implications for clinical neonatal care and perinatal care quality research and audit. A literature review of clinical findings and their validity in HIE was conducted in response to a need identified by the National Patient Safety Association, the National Perinatal Epidemiology Unit and a systematic review of international population-based data. The literature review found heterogeneous descriptions of clinical findings and clinical definitions in HIE, with no study to date either comparing clinical findings in HIE with those in neonatal encephalopathy due to other causes, or validating a clinical definition using imaging techniques. A subsequent literature review found that MRI and magnetic resonance spectroscopy have been found to have good specificity and sensitivity for diagnosis of HIE. This review, together with an ongoing national clinician consensus-building exercise led by the NPEU have led to the designing of a retrospective study to serially revise and validate a simple definition of HIE for future clinical and research use in order to improve the quality of epidemiological, health care quality and therapeutic research into HIE.